THE INFLUENCE OF FINANCIAL RATIOS AGAINST GROWTH OF PROFITS AT MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Ning Tiyas, Kartika Hendra Titisari & Siti Nurlaela (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This research aims to know the influence of current ratio, debt to equity, return on assets, return on equity, and net profitmargin against profit growth at the company's manufacturing Indonesia stock exchange. The data used are secondary datafrom the Indonesia capital market financial report directory (ICMD). The population of this research all the manufacturingcompanies listed on the Indonesia stock exchange. The samples used in the study was 63 manufacturing companies listed onthe Indonesia stock exchange. Method of determination of the sample used by using purposive sampling. Results descriptivestatistics show that current ratio value is quite high compared to other variables, this indicates that the high short-termpayment companies rather than increase its own capital to guarantee debt . Based on the correlation analysis shows thevariable current ratio, debt to equity ratio, return on assets, and net profit margin is correlated with positive and significantprofit growth supported by empirical evidence, while the return on equity is correlated negative and significant profit growthsupported by empirical evidence.Keywords: Liquidity; Solvency; Profitability; the profit growth